A fé do interior: uma história de coragem do povo nordestino - Santos, Raissa Nascimento dos (2016)
This report reflects on the characteristics - proximities and peculiarities - of journalism and biography. After the theoretical debate on concepts such as truth and time in both worlds, the research aims to present the product, the book-report: The Faith from the Countryside – A history of courage of the northeastern people. The work chronicles the lives of four generations of a family in the rural area of Pernambuco struggling to win the main battle that life offers , the drought that punishes the region . Throughout the narrative, woven through literary journalism, new battles are presented in the life of this brave people, rescuing more than a century of history.